IMPULSE BUYING OF GENERATION Z MUSLIMS: A STUDY ON HEDONIC SHOPPING MOTIVATION, SHOPPING LIFESTYLE, AND HEDONIC SHOPPING VALUE - Setiawan, Muhammad Afan; Supriyanto, Agus (Economic and Science Faculty of Islamic State University, 2023)
The aim of this study was to identify the factors influencing impulse buying among Generation Z Muslims in Kudus Regency. The research was conducted on the Generation Z Muslim community in Kudus Regency, with a total sample size of 100, utilizing the purposive sampling technique. Data processing involved the use of statistical analysis methods through the SPSS program. The findings of this study revealed that the hedonic shopping motivation variable did not exhibit a positive and significant impact on impulse buying among Generation Z Muslims in Kudus Regency. Conversely, the Shopping Lifestyle variable demonstrated a positive, albeit insignificant, effect on impulse buying behavior of Generation Z Muslims in Kudus Regency. Moreover, the Hedonic Shopping Value variable exhibited a positive and significant influence on impulse buying among Generation Z Muslims in Kudus Regency. The managerial implication of this research underscores the importance of considering shopping lifestyle behavior and hedonic shopping value, as these factors can have an impact on the impulse buying tendencies of Generation Z Muslims.